Access to Disclosure of Disasters Information for Deaf People through Sign Language Interpreter - Fauziyah, Siti; Jannah, Lina Miftahul (Indonesian Journal of Disability Studies, 2022)
There are plenty of information or news regarding natural disasters being inaccessible for Deaf people, and this stems from lack of Sign Language Interpreters. Urgency Sign Language Interpreters have an important role in bridging communication between society and the entire Deaf population, Sign Language Interpreters can also help people with Deafness in accessing information comprehensively on the aforementioned subject (natural disasters). Mostly, Deaf people communicate through sign language in their everyday lives, although Deaf people are still experiencing exclusion in discerning the newest and developing information on the current state of world affairs. This study aimed to elaborate situations faced by Deaf people in accessing information on natural disasters around them, their needs on accessing said information, and also urgency as well as obstacles faced in providing Sign Language Interpreters. This research will use qualitative approach by means of document/literature study to gather data from various international as well as national articles in general.